Energy literacy of vocational students in Taiwan. Issue 6 (3rd July 2017) - Lee, Lung-Sheng; Chang, Liang-Te; Lai, Chih-Chien; Guu, Yunn-Horng; Lin, Kuen-Yi
Abstract : In this study, we administered a questionnaire to 1001 vocational high school students to ascertain their literacy with regard to energy saving and carbon-emissions reduction (ESCER) and to analyze whether their literacy was affected by their gender or academic major. The data analysis produced the following conclusions: (1) behaviors pertaining to ESCER among vocational high school students should be enhanced by promoting appropriate affect rather than solely by conveying knowledge; (2) female students displayed superior knowledge and affect regarding ESCER compared with male students; and (3) students majoring in agriculture performed better than other students in terms of knowledge, affect, and behavioral aspects related to ESCER. The execution and results of this study can serve as a reference for courses or education related to this topic targeting vocational high school students to promote literacy for ESCER, thereby increasing students' effectiveness in related issues in Taiwan.